Implementation of Targeted Point of Care HIV Testing in a Pediatric Emergency Department. Issue 1 (January 2020) - Bhatt, Seema R.; Eckerle, Michelle D.; Reed, Jennifer L.; Robinson, Venita; Brown, Angela; Lippe, Joyce; Holland, Carolyn; Iyer, Srikant
Abstract : Introduction: HIV infection rates are increasing among adolescents. Despite guidelines recommending annual HIV screening among sexually active adolescents, 3.6% of adolescents tested for other sexually transmitted infections (STI) in a pediatric emergency department (PED) were screened for HIV. The aim was to increase HIV screening to 90%. Methods: Interventions were designed to address 4 key drivers thought to be critical in reliably offering HIV testing. The primary outcome measure was the proportion of adolescents offered HIV testing among those being tested for common STIs. Statistical process control charts were used to measure performance over time and differentiate common versus special cause variation. Results: We instituted point of care (POC) HIV testing in the PED in January 2012. The proportion of STI tested patients offered HIV testing was increased to >87% and sustained this performance. Implementation of a clinical decision support tool had the highest impact. The majority offered testing agreed, and the most common reason for refusal was a recent negative test. We identified eleven HIV positive patients over 5 years. Eight were newly diagnosed, and 3 had prior positive tests but were not connected to care. All 11 were successfully connected to providers with HIV care expertise. Conclusions: POC HIV testing is feasible, acceptable, and sustainable in a PED setting. The implementation of targeted HIV POC testing in the PED increased the number of HIV tests being offered, the number of high-risk patients being screened, and the number diagnosed and connected to care.